Cutaneous Ulcerative Disease in a Star Tortoise - Veeraselvam; Tamileniyan, E; Jeevitha, M; Yogeshpriya S; Karthika, K. Jyothipriya, R; Ponnu swamy, K.K (Indian Journal of Veterinary Medicine, 2025)
A rescued Indian Star Tortoise (Geochelone elegans) was presented with shell deformities, limb weakness and ulcerative plastron lesions. Clinical evaluation, radiography and biochemical analysis were carried out. The plastron was abnormally soft and pliable, deviating markedly from the rigidity observed in healthy individuals. Deep ulcerative lesions were noted on the pectoral and abdominal scutes of the plastron. Hypocalcaemia with elevated phosphorus, parathyroid hormone and alkaline phosphatase levels was observed while reduced serum vitamin A and 1,25-dihydroxycholecalciferol concentrations. Microbiological culture of the ulcerative plastron lesions yielded Escherichia coli and Staphylococcus spp. Treatment included calcium and vitamin supplementation, fluid therapy and antimicrobial therapy, resulting in significant clinical improvement and shell remineralization within six weeks.